Investigating the Surface Morphology and Composition of the Methyl Orange by Different Spectroscopic Techniques - Yadav, Chandradip Kumar; Jha, Susmita; Jha, Randhir Kumar; Rakesh, Benadict; Mohapatra, Adyasha Swain; Nath, Deepak; Gautam, Madhab; Bhattarai, Ajaya (Butwal Campus Journal, 2025)
Weak organic acids and bases function as pH or common anionic indicators for determining the endpoint in neutralization titrations. Methyl orange, a commonly used indicator, appears red in acidic conditions and yellow in alkaline solutions. In this study, surface and spectroscopic analyses were employed to characterize methyl orange. Energy Dispersive X-ray (EDX) analysis was conducted to determine its elemental composition, revealing that approximately 66% of the sample consists of carbon, along with about 24% of oxygen, sulfur, sodium, and other elements. The crystalline nature of the sample was confirmed through X-ray Diffraction (XRD) and Field Emission Scanning Electron Microscope (FE-SEM) analysis. Furthermore, Fourier Transform Infrared (FT-IR) Spectroscopy identified the presence of amino groups and double-bonded carbon atoms within the aromatic system. Raman spectroscopy, particularly in the 1000–1700 cm-1 range, further validated the findings from FT-IR. This study serves as a significant contribution to the comprehensive characterization of methyl orange.